Cybernetics - the Macy Conferences 1946-1953 the complete transactions - Macy Conference New York, NY 1946; Pias, Claus <1967->; Diaphanes (Zurich ; Berlin : Diaphanes, 2016)
Dokumentiert 5 Macy-Konferenzen von 1946 bis 1953
Keywords: Konferenzschrift / , 1946-1953; Kybernetik; Systemtheorie; Informationstheorie; Steuerungstheorie